Emergence of MRSA ST612 in horses and of MSSA CC398 in cats in France - Haenni, Marisa; Murri, Séverine; Drapeau, Antoine; Rafidinarivo, Iarimino; Gilles, Stéphanie; Keck, Nicolas; Léon, Albertine; Sulter, Aline; Tricaud, Marie-Capucine; François, Pauline; Madec, Jean-Yves (Journal of antimicrobial chemotherapy, 2025)
Staphylococcus aureus is an important zoonotic pathogen that has often been seen in animals through the prism of the MRSA clonal complex (CC) 398 in pigs and in-contact humans. The goal of this study was first to assess the prevalence of MRSA, and second to look for MSSA CC398 in cats, dogs and horses in France. Clinical S. aureus isolates (n = 479) were collected from 186 cats, 143 dogs and 150 horses during 2022-2023 all over the French territory. Antibiograms were performed on all isolates. MRSA and MSSA CC398 isolates were subject to WGS. Core genome (cg) MLST-based and SNP-based phylogenetic analyses were performed using published methodologies, and characterization of the isolates was performed using publicly available tools. Sixty-six MRSA isolates were identified in 14 cats (7.5%), 9 dogs (6.3%) and 43 horses (28.7%). The epidemiology of MRSA in cats and dogs remained stable since a previous study in 2015, with the presence of both CC398 and human-associated clones. In horses, in contrast, an important increase in MRSA (from 10% to 28.7%) was observed, potentially attributable to the emergence of the ST612 clones. In parallel, CC398 MSSA, a clone usually described as animal-independent, was found in 24.2% of the cat isolates. Our study, which is leading the way to a genomic surveillance of S. aureus in France, revealed the emergence of both MRSA ST612 in horses and MSSA CC398 in cats. These clones should be closely monitored to avoid their zoonotic spread and to understand their dynamics of transmission between humans and animals.